Rigging System Design in Character "Gery” for 3D Character Animation Course - Sumampouw, Eldwin Manuel; Pratama, Tito Ari (ULTIMART Jurnal Komunikasi Visual, 2024)
A well-planned rigging system design will make it easier for an animator to animate a model. A rigging system is designed to create a controller hierarchy and a joint reinforcement hierarchy to move a model. The rigging system must be created to develop user comfort and to design an efficient system to make it easier for animators to animate the model. This study aims to create an original model named Gery along with a rigging system design that is comfortable and efficient, especially in the design of an innovative facial rigging system. In this study, the author will observe the Stewart model as the foundation for designing the body rigging system and the Mery model as the foundation for designing the facial rigging system. The author applies the leading theory of the rigging system workflow created by Cheryl Briggs as a guideline in the production stage of the work. The author also applies the supporting theory of the body rigging design plan created by Eric Allen & Kelly L. Murdock and the application of the FACS theory reference compiled by Brigita C. Beavis as a guideline in the pre-production stage. The results of this identification will form the basis for designing the Gery model rigging system. This system is efficient and comfortable for learning 3D character animation courses. Keywords: rigging 3D; body rigging; facial rigging